Exploring beliefs about heart failure treatment in adherent and non-adherent patients: Use of the repertory grid technique - Cottrell, W.; Denaro, C.; Emmerton, Lynne (Dove Medical Press Limited, 2013)
Purpose: Beliefs about medicines impact on adherence, but eliciting core beliefs about medicines in individual patients is difficult. One method that has the potential to elicit individual core beliefs is the “repertory grid technique.” This study utilized the repertory grid technique to elicit individuals’ beliefs about their heart failure treatment and to investigate whether generated constructs were different between adherent and nonadherent patients. Methods: Ninety-two patients with heart failure were interviewed using a structured question¬naire that applied the repertory grid technique. Patients were asked to compare and contrast their medicines and self-care activities for their heart failure. This lead to the generation of individual constructs (perceptions towards medicines), and from these, beliefs were elicited about their heart failure treatment, resulting in the generation of a repertory grid. Adherence was measured using the Medication Adherence Report Scale (MARS). Patients with a MARS score $ 23 were categorized as “adherent” and those with a score # 22 as “nonadherent.” The generated grids were analyzed descriptively and constructs from all grids themed and the frequency of these constructs compared between adherent and nonadherent patients. Results: Individual grids provided insight into the different beliefs that patients held about their heart failure treatment. The themed constructs “related to water,” “affect the heart,” “related to weight,” and “benefit to the heart” occurred more frequently in adherent patients compared with nonadherent patients.Conclusion: The repertory grid technique elicited beliefs of individual participants about the treatment of their heart failure. Constructs from self-reported adherent patients were more likely to reflect that their medicines and self-care activities were related to water and weight, and affect and benefit to the heart. Providing clinicians with better insight into individuals’ beliefs about their treatment may facilitate the development of tailored interventions to improve adherence.